Antioxidant and Anti-inflammatory Activity of Ethanol Extracts from Sambal Orange Peel (Citrus microcarpa Bunge) on Erythrocyte Membrane Stabilization - Sukandiarsyah, Fadli; Hayati, Defi Nurul; Sari, Vina Purnama; Riska, Bella (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
Inflammation is the body's defense response to various stimuli. Sambal orange (Citrus microcarpa Bunge) belongs to the Rutaceae family and is widely cultivated in West Kalimantan. This study uses the erythrocyte membrane stabilization method to test the secondary metabolite content, antioxidant activity, and anti-inflammatory activity of ethanol extracts of sambal orange peel. Antioxidant activity was assessed using the DPPH method, while anti-inflammatory activity was evaluated through erythrocyte membrane stabilization. The results showed that the extract had an antioxidant IC50 value of 17.90 ppm, which is very strong. Membrane stability at concentrations of 50, 100, 150, 200, and 250 ppm showed increases of 32.20%, 38.39%, 47.37%, 55.18%, and 65.52%, respectively. The % stability values of sodium diclofenac at the same concentrations were 50.10%, 58.40%, 66.69%, 78.59%, and 87.70%, respectively. The one-way ANOVA test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between treatments. The Tukey post-hoc test showed no significant difference between the 250 ppm extract concentration and the 150 ppm sodium diclofenac concentration. The IC50 value for the extract's anti-inflammatory activity was 163.55 ppm (moderate activity), while sodium diclofenac exhibited stronger activity with an IC50 value of 54.09 ppm.